Malay Concept of Time, Space and Motion as Understood from Classical Texts of History - Othman, Hussain (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Malay Concept of Time, Space and Motion as Understood from Classical Texts of History